An intrinsic cytoskeletal oscillator establishes neuronal polarity - Tien-chen Lin; Charlotte H. Coles; Eissa Alfadil; Florian Fäßler; Andreas Husch; Sebastian Dupraz; Thorben Pietralla; Akihiro Narita; Max Schelski; Kevin C. Flynn; Sina Stern; Christoph Möhl; et al. (Nature, 2026)
Abstract Neurons acquire polarity by specifying one neurite as the axon, whereas the others become dendrites. But how this fundamental asymmetry is established remains unclear 1 . Neuronal polarization has been thought to rely primarily on growth cones that sense external cues 2 . Here we show that growth cones alone do not direct this process and that the soma acts as a central organizer of neuronal polarization. Using live imaging and genetic loss-of-function approaches in vivo, combined with optogenetic control and local cytoskeletal perturbations in cultured neurons, we uncover a soma-initiated oscillatory program that primes axon selection. Periodic actin branching that depends on the actin-related protein 2/3 (ARP2/3) complex at the soma remodels a global actomyosin network, thereby generating an actin wave that retracts neurites before propagating into a single neurite tip. Exposure to this wave relaxes local actomyosin contractility, which drives a transient microtubule-based protrusion and biases this neurite towards axon fate. As the cell exits this oscillatory stage, this neurite can overcome global inhibition and extend independently of ARP2/3, whereas actomyosin activity suppresses axon formation in the remaining neurites so that they subsequently become dendrites. This soma-driven mechanism ensures the emergence of a single axon independent of environmental cues and underpins the unidirectional information flow in neuronal circuits.